Travel and “Homing In” in Contemporary Ethnic American Short Stories - Maszewska, Jadwiga (Text Matters: A Journal of Literature, Theory and Culture, 2012)
In American ethnic literature of the last three decades of the 20th century, recurrent themes of mobility, travel, and “homing in” are emblematic of the search for identity. In this essay, which discusses three short stories, Alice Walker’s “Everyday Use,” Louise Erdrich’s “The World’s Greatest Fishermen,” and Daniel Chacon’s “The Biggest City in the World,” I attempt to demonstrate that as a consequence of technological development, with travel becoming increasingly accessible to ethnic Americans, their search for identity assumes wider range, transcending national and cultural boundaries.